Effects of corrugation on convective heat transfer and power generation in a wavy walled triangular cavity equipped with inclined elastic fin and piezo-energy harvester assembly - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier, 2024)
Piezoelectric energy harvesters are one of the energy conversion technologies that can be used to convert a variety of external sources, including wind, fluid motion, and vibrations, into electrical energy. This work suggests a novel wall corrugation design in addition to an elastic fin piezo assembly arrangement for power generation and thermal management in a triangular cavity during turbulent forced convection of air. Using the finite element method with ALE, the analysis is conducted for different values of fin inclination (gamma between 0 and 60), corrugation amplitude (Af between 0.01H and 0.06H), corrugation frequency (Nf between 1 and 20) and fin distance from the mid-point of the inclined wall in wall direction. The average Nusselt number (Nu) and generated power (PW) show a non-linear increasing trend with increasing fin tilt. Average Nu increment factor becomes 5.17 with the highest fin inclination while the power increments become 11.6 and 4.46 when rising inclination from 30 to 45 and from 45 to 60. The generated power rises with higher corrugation amplitude and wave number. However, increasing the wave number results in thermal performance degradation. Increment of average Nu becomes 1.17 with highest corrugation amplitude while it declines by a factor of 10.3 at the highest wave number. Power enhancement factors of 5.73 and 2.32 are obtained by increasing the corrugation amplitude from Af = 0.0714H to Af = 0.1786H and from Af = 0.1786H to Af = 0.2143H. When fin positions sf = 0.7143H and sf =-0.7143H are compared with the case of fin location at sf = 0, the power increment factors become 12.27 and 4.76, respectively. For the power produced by the piezo device, a polynomial type correlation is suggested by adjusting the parameters of the corrugated wall.
Keywords: Wavy wall; Piezo energy harvesting; Finite element method; Turbulent forced convection; Triangular cavity